Synthesis and studying of reduced few-layered graphene coatings in gas sensor applications. (March 2019) - Lukosevics, Ingars; Lesnicenoks, Peteris; Kleperis, Janis
Abstract: In this work reduced few-layered graphene (rFLG) nanoparticles were synthesized using electrochemical pulse exfoliation method from waste graphite crucibles. The regular change in voltage polarity in the synthesis process ensures both the separation of graphite in layers and the reduction of graphene oxide. A method for synthesizing free-standing rFLG and nitrocellulose (NC) composite film has been developed involving creation of rFLG-NC ink that can be deposited on various substrates. It has been observed that a successful synthesis of a free-standing composite coating is possible with the mass ratio of rFLG:NC at least 9:1 of which resistivity is on the order of approximate 10 ohm-centimetres in dependence from temperature and surrounding atmosphere. Sensor electrode was prepared by simple dip-coating method and the response to humidity, organic solvent vapours and nitrogen containing gases was measured and conclusion made that rFLG-NC coating is sensitive to many kinds of gases (cross-sensitive) what may result in false detecting or can be used to multi-sensor chips for artificial olfaction devices.